Using approximate Bayesian computation to quantify cell–cell adhesion parameters in a cell migratory process - Robert J. H. Ross (Nature Portfolio, 2017)
Math heals: Using computational methods to improve design of wound healing assay Cell motility is a central process in wound healing and relies on complex cell-cell interactions. A team of mathematicians led by Ruth Baker and Kit Yates at the University of Oxford utilised computer simulations to re-design wound-healing assays that efficiently identify cell motility parameters. New experimental designs through computer simulation can more accurately identify cell motility parameters by expanding the size of the domain upon which the experiment is performed, as opposed to increasing the number of experimental replicates. The results describe time and cost-saving alterations for an experimental method for evaluate complex cell-cell interactions.